Odpowiedzi

Najlepsza Odpowiedź!
2010-02-07T14:36:27+01:00
1. a) 2x+3/5=2-x/3-x /*15
30x+9=30-5x-x
30x+5x+x=30-9
36x=21
x=7/12

b) x+1/2-x-1/3=1/4 /*12
12x+6-12x-4=3
-12x=3-12-6+4
-12x=-11
x=11/12

c) 4x+7/2-5x-1/6=x+5 /*6
24x+21-30x-6x=30-21+1
-12x=10
x=-10/12
x=-5/6

d) x+5/4-2x+1/8=1/2(2-x) /*4
4x+5-8x+1/2=2(2-x)
4x+5-8x+1/2=4-2x
4x-8x+2x=4-5-1/2
-2x=-3/2
x=3/4

2. a) 1/2x-3/4[x-(4x+1)]=1-x+1/4 /*4
2x-3[x-4x-1]=4-4x+1
2x-3x+12x+3=5-4x
11x+4x=5-3
15x=2
x=7,5

b) 2/3(3x-1)-3/2[2x+3(x-2)]=1 /*6
4(3x-1)-9[2x+3x-6]=6
12x-4-18x-27x+54=6
-33x=6+4-54
-33x=-44
x=44/33
1 1 1